Cone-valued impulsive differential and integrodifferential inequalities - Sam Olatunji Ale; Benjamin Oyediran Oyelami; Maligie S. Sesay (Electronic Journal of Differential Equations, 2005)
In this paper, we present impulsive analogues of the Gronwall-Bellman inequalities. Conditions for the existence of maximal solutions of some integrodifferential equations are obtained by finding upper bounds for these inequalities. Using monotone iterative techniques and a fixed point theorem, we obtained a priori estimates for the inequalities.